Regimes of happiness : comparative and historical studies - Contreras-Vejar, Yuri; Jen, Joanna, Tice; Turner, Bryan S. (Anthem religion and society series, 2019)
'Regimes of Happiness' is a comparative and historical analysis of how human societies have articulated and enacted distinctive notions of human fulfillment.